Synthesis of nitrogen, phosphorus, selenium and sulfur-containing heterocyclic compounds - Determination of their carbonic anhydrase, acetylcholinesterase, butyrylcholinesterase and α-glycosidase inhibition properties - Gülçin, İlhami; Trofimov, Boris; Kaya, Ruya; Taslimi, Parham; Sobenina, Lyubov; Schmidt, Elena; Petrova, Olga; Taslimi, Parham (Academic Press Inc Elsevier Science, 2020)
Sulfur-containing pyrroles (1-3), tris(2-pyridyl)phosphine(selenide) sulfide (4-5) and 4-benzyl-6-(thiophen-2-yl)pyrimidin-2-amine (6) were synthesized and characterized by elemental analysis, IR and NMR spectra. In this study, the synthesized compounds of nitrogen, phosphorus, selenium and sulfur-containing heterocyclic compounds (1-6) were evaluated against the human erythrocyte carbonic anhydrase I, and II isoenzymes, acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and alpha-glycosidase enzymes. The synthesized heterocyclic compounds showed IC50 values in range of 33.32-60.79 nM against hCA I, and 37.05-66.64 nM against hCA II closely associated with various physiological and pathological processes. On the other hand, IC50 values were found in range of 13.13-22.21 nM against AChE, 0.54-31.22 nM against BChE, and 13.51-26.55 nM against alpha-glycosidase as a hydrolytic enzyme. As a result, nitrogen, phosphorus, selenium and sulfur-containing heterocyclic compounds (1-6) demonstrated potent inhibition profiles against indicated metabolic enzymes. Therefore, we believe that these results may contribute to the development of new drugs particularly in the treatment of some global disorders including glaucoma, Alzheimer's disease and diabetes.
Keywords: Pyrrole; Carbonic Anhydrase; Enzyme Inhibition; Alpha-Glycosidase; Acetylcholinesterase, Butyrylcholinesterase